Edukasi Dan Pemberdayaan Masyarakat Desa Sungai Pinang Melalui Pembuatan Eco-enzym Sebagai Pupuk Organik Cair - Erlinawati Erlinawati; Dian Pani Safitri; Muhammad Noviansyah Nugraha; Sahrul Effendy A; Wahyu Triaji Rahadianto (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Sungai Pinang Village, Rambutan District, Banyuasin Regency is an area with agricultural and household activities that generate a significant amount of organic waste, particularly vegetable residues and fruit peels. However, the utilization of this waste is still not optimal and is often discarded, potentially causing environmental pollution. Therefore, this community service activity aims to provide education and empower the community in processing organic waste into eco-enzyme as an environmentally friendly liquid organic fertilizer. The method used is an educative-participatory approach through observation, surveys, socialization, and direct practice in making eco-enzyme. This activity actively involves the community in the waste processing stages, including material collection, mixing, and fermentation. The results indicate an increase in community knowledge and understanding of organic waste management, as well as the ability to independently produce eco-enzyme. Furthermore, the eco-enzyme produced can be utilized as a liquid organic fertilizer to support the growth of horticultural plants in home gardens. Thus, this activity not only provides a solution to waste problems but also supports sustainable agricultural practices. Overall, this program plays an important role in increasing environmental awareness and community independence in managing organic waste.